Comparative evaluation of intravaginal slow release Dinoprostone insert, transcervical foley’s catheter, intracervical Dinoprostone gel for induction of labor in patients with poor Bishop’s score: a randomized control study - Gupta, Taru; Singh, Ritu; Gupta, Nupur; Gupta, Sangeeta; Singal, Khushbu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Induction of labor is indicated when the continuation of pregnancy poses risk to the mother or fetus. A variety of mechanical and pharmacologic methods are available but the best method of labor induction still remains unknown, study aimed at comparing the efficacy and safety among the two agents: transcervical Foley’s balloon catheter (FBC) and intravaginal slow release Dinoprostone E2 insert (DVI) with dinoprostone gel as control. Methods: A total of 174 patients were randomized into three groups of 58 each (Group A: dinoprostone 10 mg slow release intravaginal insert, Group B: transcervical Foley’s 16 French catheters, and Group C as control: 0.5 mg intracervical Dinoprostone gel. The safety and efficacy was compared among the groups. A p value of < 0.05 was considered statistically significant. Results: The mean insertion to active labor time (in hours) was significantly lower in Group A as compared to Group B (5.88±3.06 versus 13.56±2.8, p < 0.0001). Meantime of insertion to delivery (in hours) was significantly lower in Group A as compared to Group B (10.91±5.24 versus 21.17±2.99, p < 0.0001). The requirement of oxytocin for induction and augmentation in Group A was significantly lower as compared to Group B. Majority of the patients had normal vaginal delivery (NVD) in all the three groups. Regarding safety profile we found that slow-release DVI had more incidence of uterine tachysystole, but none of the cases had any fetal heart rate abnormality. Maternal fever was more in the FBC group, however, neonatal outcomes were comparable in both groups. Conclusions: The study concludes that slow release DVI is better in terms of efficacy as compared to transcervical FBC for induction of labor as assessed by improvement in Bishop score, insertion to active labor time and insertion to delivery time and comparable in terms of safety profile.